The effect of introducing a free breakfast club on eating habits among students at vocational schools - Camilla Berg Christensen; Bent Egberg Mikkelsen; Ulla Toft (BMC, 2019)
Abstract Background Unhealthy eating habits are a major problem among adolescents. The objective of the study was to assess the effect of a free breakfast club intervention on dietary habits among students at vocational schools. Methods The study included students (n = 318) from four vocational schools in Denmark. Food frequency questionnaires were used to measure eating habits at baseline, first, and second follow-up, after 7 and 14 weeks respectively, in a clustered randomized controlled intervention of four months. The effect of the intervention was evaluated through self-reported frequencies of breakfast intake, intake of whole grain products for breakfast and intake of unhealthy snacking in the morning. The outcome measures were daily breakfast intake (yes/no), daily intake of whole grain for breakfast (yes/no), and unhealthy snacking on school day mornings (yes/no). Results The proportion of students who had breakfast every school day increased significantly in the intervention schools from baseline to the first follow-up compared to the control group (OR: 3.77; P = 0.0149). The effect was attenuated at the second follow-up. The intake of whole grain products for breakfast increased significantly more among students in intervention schools compared to students in control schools both at first (OR: 4.13; P = 0.0079) and second follow-up (OR: 3.27; P = 0.0317). No significant change in unhealthy snacking was found. Conclusion Provision of free breakfast at vocational schools can improve the dietary quality of breakfast and decrease breakfast skipping. However, the sustainability of the intervention is a critical issue that needs to be further studied and addressed. Trial registration ISRCTN11265280. Registered 20 November 2018 (retrospectively registered).